A Guideline for Double Skin Facades in an Initial Design Phase: Applying Cross Ranking and Fuzzy Logic Methods for Temperate Climate Region - İlter, Sertaç (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Climate change and global warming have become a quandary for today and as a result architects faced with unexpected design process issues. In this context, expected performance requirements of building façades advanced to beyond of being resistant against the environmental effects of such as wind and rain forces and transfer of the loads. Expected requirements also include becoming active to keep constant user comfort under flexible climate conditions also using renewable energy sources for energy conservation and being able to adapt itself when its needed to reach a certain level of economic sustainability. Architects used numerous façade systems in their projects; currently double skin façade systems become the most common façade system in use to meet these expectations. This thesis aimed to develop a scale that can be utilized during the early design stage to identify potential risks that can be faced after the construction process for a façade system, which can adapt itself according to different requirements of users and dynamic external factors. Designers may have the possibility to evaluate their designs using the recommended value of risk assessment during the early design stage. Keywords: Double Skin Façade, Intelligent Envelopes, Design Strategies, Occupant Comfort

ÖZ: Mimarların ufuktaki hedefi yaşam çevresini tekrar düzenlemek ve bunu yaparken yapılaşmaya ve dünya ya tekrar bir bakış açısı kazandırmaya çalışmaktır. Global dünyanın sorunu haline gelen küresel iklim değişiklikleri bugünün tasarımcılarını bilinmeyene yada tahmin edilemeyene karşı bir tasarım süreci ile karşı karşıya bırakmıştır. Bu bağlamda, bina cephelerinden beklenilen performans gereksinimleri dayanıklı olmaları, yükleri aktarmaları, rüzgara, kara ve yağmura karşı dayanımlı olabilmenin ötesine geçmiş ve kullanıcı konforunu değişken iklim şartları altında sabit tutabilmek ve ekonomik açıdan sürdürülebilirlik sağlayabilmek için enerji korunumu, yenilenebilir enerji kaynaklarında yararlanabilmek ve ihtiyaç doğrultusunda değişkenlik göstermek gibi bazı yeni gereksinimleride karşılamaları beklenmektedir. Bu beklentileri karşılamak adına mimarlar çeşitli cephe sistemlerini yapılarında kullanmışlardır, günümüzde ise en yaygın cephe sistemi olarak çift cidarlı cepheler ön plana çıkmaktadır. Bu tezde, dış faktörlerin karakterlerine ve faklı kullanıcı gereksinimlerine uyum sağlayabilme özelliği gösterebilen değişken yapı kabuklarını baz alarak mimarlara yapım sürecinden sonra karşılaşılabilecek riskleri belirlemek amacı ile tasarım surecinde faydalanılabilecek bir skala geliştirilmeye çalışılmıştır. Tasarımcılar, önerilen risk değerlerini kullanarak tasarımını değerlendirme olanağına sahip olabilirler. Anahtar Kelimeler: Çift Cidarlı Cepheler, Akıllı Cepheler, Tasarım Stratejileri, Kullanıcı Konforu
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assoc. Prof. Dr. Müjdem Vural.
Keywords: Facades--Architectural Design; Double Skin Façade; Intelligent Envelopes; Design Strategies; Occupant Comfort; Architecture